Edukasi Teknologi Smart Recycling ATM Sampah Botol Plastik Berbasis Aplikasi Tabungan Anak untuk Mendorong Ekonomi Sirkular di Sekolah - Deasy Rosanti Nurjannah; Iwan Kustiawan; Saripudin Saripudin (Universitas Pahlawan Tuanku Tambusai, 2026)
Plastic waste management in schools remains a major challenge, particularly in improving students’ awareness and habits regarding waste sorting and recycling. This community engagement program aimed to develop and implement a Smart Recycling ATM at Al-Lathif Islamic School Bandung, enabling students to exchange plastic bottles for digital savings balances through the EcoCash application. A participatory approach was applied by involving teachers and students in each stage of the program, including needs assessment, device installation, socialization, mentoring, and evaluation. The results showed that the program reduced plastic waste volume by 40% in the first month. In addition, 72% of students actively used the savings application to monitor their plastic bottle deposits. The program also improved students’ understanding of plastic-bottle recycling into 3D-printing filament and the circular economy in the school context. Therefore, technology-based environmental education can contribute positively to fostering ecological and financial awareness among children from an early age.